1992
DOI: 10.1103/physrevlett.68.1061
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate magnetic correlations inLa1.8Sr0.2

Abstract: Neutron scattering experiments on an insulating single crystal of Lai.sSnuNiC^ show the presence of strong two-dimensional incommensurate magnetic correlations in the NiCh planes. At low temperatures, r = 2 K, these exist on time scales r > 10 ~M s. The typical side length of the correlated regions in the direction parallel to the incommensurate modulation is equal to the average spacing between strontium atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
81
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 21 publications
5
81
0
Order By: Relevance
“…The simultaneous appearence of charge and spin superstructures seems to be present in completely different systems. For example, charge, lattice and spin modulations with a doping-dependent wave vector have been observed in La 2−x Sr x NiO 4 by means of neutron scattering [1] and electron diffraction [2]. Stripe formation, together with incommensurate spin fluctuations in high Tc superconductors can also be regarded as a manifestation of similar phenomena [3].…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous appearence of charge and spin superstructures seems to be present in completely different systems. For example, charge, lattice and spin modulations with a doping-dependent wave vector have been observed in La 2−x Sr x NiO 4 by means of neutron scattering [1] and electron diffraction [2]. Stripe formation, together with incommensurate spin fluctuations in high Tc superconductors can also be regarded as a manifestation of similar phenomena [3].…”
Section: Introductionmentioning
confidence: 99%
“…excitations at incommensurate wavevectors [4], have been interpreted as evidence for dynamic stripe correlations [5]. At the same time, the characteristic spin excitation spectrum of ideal stripes has been probed in studies of non-superconducting compounds with well defined stripe order, especially La 2−x Sr x NiO 4+δ [6,7]. In none of these previous studies, however, has any evidence been found for spin correlations among the stripe electrons themselves.…”
mentioning
confidence: 99%
“…Historically, the first evidence for unusual magnetic correlations was obtained in doped nickel oxide, namely on a single crystal of La 1.8 Sr 0.2 NiO 3.96 in a neutron diffraction study [1]; similar magnetic ordering was also observed in La 2 NiO 4.125 [2]. A second set of superlattice peaks, indicative of charge order, was detected in a series of La 2-x Sr x NiO 4+d samples by electron diffraction [3].…”
Section: Introductionmentioning
confidence: 92%
“…The unit-cell vectors a 1 and a 2 are parallel to nearest-neighbor Ni-O bonds within the planes, and a 3 is perpendicular to the planes. There are two NiO 2 planes per unit cell, and they are related by the basic vector 1 2 a 1 + 1 2 a 2 + 1 2 a 3 . For each Ni ion there is one out-of-plane oxygen atom directly above and one atom below (along a 3 axis) effectively completing a tetragonally-distorted octahedron of oxygen ions.…”
Section: Introductionmentioning
confidence: 99%